Hour of the bees - Eagar, Lindsay (Candlewick Press, 2017)
Twelve-year-old Carolina meets her grandfather, Serge, when her family travels to Albuquerque to sell Serge's sheep ranch and help him move into a nursing home. Carol hates to miss part of her summer, but changes her mind when Grandpa begins telling her stories about her heritage, of the magic tree that heals, of a green-glass lake, of 100 years of no rain, and of the magical bees that brought the rain back.